(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
In linguistics, various gender categories and their reflection in vocabulary are important, as well as the role of gender in the formation of the meanings of words. For example, various types of gender semantics, such as gender stereotypes and gender metaphors, have a semantic manifestation in English vocabulary.